Notas do inacabado, uma leitura do processo de criação de A ferro e fogo, de Josué Guimarães - Rech, Mônica Golfetto (2012)
Research performed with the works and prototexts from writer and journalist Josué Guimarães are still disproportional concerning its importance in the literature of Rio Grande do Sul and Brazil. This work presents a study on the work of Josué Guimarães, focusing on the process of constructing the unfinished trilogy A ferro e fogo, initially planned by the author as a narrative about German immigration, and especially about the Muckers in the incidents involving the location of São Leopoldo in the late XIX century. As an unfinished project, the work was limited to two volumes, Tempo de solidão and Tempo de guerra . The process of literary creation of A ferro e fogo was investigated from the interpretation of the prototexts guarded in the Literary Collection of the author Acervo Literário de Josué Guimarães (ALJOG), in the light of the theoretical assumptions of genetic criticism and semiotics, in a perspective that investigates the complexities (or discontinuities) that affect the process of literary writing. Genetic criticism is not limited to the study of literary manuscripts, considering an indisputable aspect: times have changed, technology is managing writing directly in digital form, and the object that should be taken as raw material for studies and analysis is, therefore the creation process itself, and not the medium in which it has developed. To evaluate and get as close as possible to the creation process, the theory of the hypertext from Katherine Hayles is used, which investigates the presence of technological aspects in handwriting. In turn, the theory of semiotics from Charles S. Pierce formats and adds artistic values to the images perceived and portrayed in the folios. On the other hand, the theory of discontinuities of literary writing from Claudia Amigo Pino allows realizing the sense and meaning through erasures and outlines in marginalia. In the case of Josué Guimarães, the manuscript in his file prevails, with all his drafts and erasures, details of his preferences and marks of his originality. Thus, it is possible to clarify these clues that the author leaves in the course of his writing, involving an entire process of creating definitive bonds that will result in the final work. With all his greatness, Josué includes everyone who may access his file, with an extremely rich and inevitably exciting material, for it is possible to feel and witness his brightness taking shape and resulting in a work considered ready, however arising from many transformations